Materia orgánica de suelos bajo encinas. Mineralización de carbono y nitrógeno (Forest Systems, 2008)
Soil characteristics under evergreen oaks forest (Quercus rotundifolia Lam.) located at the East of Segovia were studied. The soils were formed from gneis and limestone. The whole soil was 0-20 cm depth. The soils were classified as mollic Leptosols, eutric Cambisols and calcaric Cambisols. Horizons sequences were the following: O, Ah1, Ah2, C and O, Ah1, Ah2, BC. Organic horizons (3-0 cm depth) were formed by the not-yet decomposed organic remains from evergreen oaks. Mean organic matter content was 25%. The C:N ratio was high and free organic carbon was near 90% of the total carbon, which correspond with a low degree of humification. Soil texture was loamy sand and sandy loam. Soils on limestone present the highest clay fraction contents. The bases saturation degree was high, being Ca 2+ the fundamental cation of exchange complex. Organic matter content and C:N ratio were lower in organic minerals horizons than in organic horizons. Humification degree was 60% with a predominance of HAs over FAs. The polimerization of humic substances makes possible the formation of humus «moder». Carbon mineralization to the total C was ten times higher than nitrogen mineralization in upper horizons. In all horizons the nitrification was higher than N mineralization. Carbon mineralization was lower and N mineralization was higher in deeper horizons compearing with upper horizons.